Dysrhythmic saliva microbiota in mobile phone addicts with sleep disorders and restored by acupuncture - Mei, Ying-Xiu; Yang, Kun; Zhang, Lu; Jin, Yue; Yang, Ni; Yang, Hong; Zheng, Ya-Li; Pang, Yue-Shan; Gong, Yan-Ju; Zhou, Hang; Zuo, Yu-Lin; Ding, Wei-Jun (Frontiers in Psychiatry, 2024)
Background: Mobile phone addiction (MPA) greatly affects the biological clock and sleep quality and is emerging as a behavioral disorder. The saliva microbiota has been linked to circadian rhythms, and our previous research revealed dysrhythmic saliva metabolites in MPA subjects with sleep disorders (MPASD). In addition, acupuncture had positive effects. However, the dysbiotic saliva microbiota in MPASD patients and the restorative effects of acupuncture are unclear. Objective: To probe the circadian dysrhythmic characteristics of the saliva microbiota and acupunctural restoration in MPASD patients. Methods: MPASD patients and healthy volunteers were recruited by the Mobile Phone Addiction Tendency Scale (MPATS) and the Pittsburgh Sleep Quality Index (PSQI). Saliva samples were collected every 4 h for 72 h. After saliva sampling, six MPDSD subjects (group M) were acupuncturally treated (group T), and subsequent saliva sampling was conducted posttreatment. Finally, all the samples were subjected to 16S rRNA gene sequencing and bioinformatic analysis. Results: Significantly increased MPATS and PSQI scores were observed in MPDSD patients (p < 0.01), but these scores decreased (p<0.001) after acupuncture intervention. Compared with those in healthy controls, the diversity and structure of the saliva microbiota in MPASD patients were markedly disrupted. Six genera with circadian rhythms were detected in all groups, including Sulfurovum, Peptostreptococcus, Porphyromonas and Prevotella. There were five genera with circadian rhythmicity in healthy people, of which the rhythmicities of the genera Rothia and Lautropia disappeared in MPASD patients but effectively resumed after acupuncture intervention. Conclusion: This work revealed dysrhythmic salivary microbes in MPASD patients, and acupuncture, as a potential intervention, could be effective in mitigating this ever-rising behavioral epidemic.